Manganese dioxide nano material, preparation method thereof and polysulfide sealant
By preparing porous structure manganese dioxide nanomaterials and combining them with polysulfide rubber, the existing problem of low manganese dioxide activity is solved, and the performance and adaptability of polysulfide rubber is improved.
Patent Information
- Application Number
- CN202411362576.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
AI Technical Summary
The existing manganese dioxide as a curing agent for polysulfide rubber has a problem of low activity, which affects the performance of polysulfide rubber.
Provide a manganese dioxide nanomaterial and its preparation method, including preparing manganese dioxide nanosheets in hydrothermal reaction through a polystyrene microsphere template, forming a porous structure of manganese dioxide nanomaterial, and placing it with polysulfur Rubber bonds to form a polysulfur sealant with highly reactive sites.
It improves the reactivity and performance of polysulfide rubber, and enhances its adaptability and application value under different conditions.
Smart Images

Figure CN119191358A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of polysulfide rubber, and specifically relates to a manganese dioxide nanomaterial and a preparation method thereof and a polysulfide sealant. Background Art
[0002] Polysulfide rubber has disulfide bonds on its main chain and thiol groups at the ends of its side chains. Its molecular weight and crosslinking rate vary with different varieties. The polysulfide reaction of polysulfide rubber is the result of two thiol groups bonding with the participation of a curing agent, generating a disulfide polymer and releasing water as a byproduct.
[0003] The existing manganese dioxide has the disadvantage of low activity when used as a curing agent for polysulfide rubber. Summary of the invention
[0004] The purpose of the present application is to provide a manganese dioxide nanomaterial and a preparation method thereof and polysulfide rubber.
[0005] The first aspect of the present application is to provide a manganese dioxide nanomaterial, the material comprising manganese dioxide nanosheets, the crystal form of the manganese dioxide nanosheets comprising any one or more of delta type, alpha type, and alpha type;
[0006] The manganese dioxide nanosheets are stacked to form a porous structure, which contains macropores with a pore diameter of 200nm to 600nm.
[0007] In some embodiments, the BET specific surface area of the manganese dioxide nanomaterial is 10 m 2 / g~50m 2 / g.
[0008] In some embodiments, the crystal form of the manganese dioxide nanosheets is delta-type, and the pore size of the macropores formed by stacking the manganese dioxide nanosheets is 400 nm to 600 nm.
[0009] The second aspect of the present application is to provide a method for preparing the manganese dioxide nanomaterial described in the first aspect, comprising the following preparation process:
[0010] providing a suspension of polystyrene microspheres;
[0011] Adding manganese salt to the suspension of polystyrene microspheres, mixing well, and forming a dispersion;
[0012] Add 20% to 30% by mass of ammonia water to the above dispersion, and react at room temperature to obtain a brown solid;
[0013] The brown solid is dispersed in an alkaline solution with a concentration of 0.5 mol / L to 6 mol / L, a solid is obtained by hydrothermal reaction, polystyrene microspheres in the solid are removed, and then a manganese dioxide nanomaterial is obtained by ultrasonic stripping.
[0014] In some embodiments, the hydrothermal reaction temperature is 120° C. to 150° C., and the reaction time is 10 h to 30 h.
[0015] In some embodiments, the method comprises: removing the polystyrene microspheres on the solid, washing with anhydrous ethanol to obtain a liquid, and ultrasonically exfoliating the liquid;
[0016] The processing time of the above ultrasonic peeling is controlled to be 4h to 24h.
[0017] In some embodiments, the mass ratio of the polystyrene microspheres to the manganese salt is (1-5):(2-5); the manganese salt includes any one or more of manganese nitrate, manganese acetate, manganese chloride, manganese sulfate and hydrated salts thereof.
[0018] In some embodiments, the weight ratio of the brown solid to the alkaline solution is 1:(10-30); the alkaline solution includes an aqueous solution of any one or more of sodium hydroxide and potassium hydroxide.
[0019] The third aspect of the present application is to provide a polysulfide sealant, which includes the manganese dioxide nanomaterial described in the first aspect or the manganese dioxide nanomaterial prepared by the preparation method described in the second aspect, and also includes polysulfide rubber.
[0020] In some embodiments, the mass percentage of the above-mentioned manganese dioxide nanomaterial in the polysulfide sealant is 3% to 10%;
[0021] and / or;
[0022] The above-mentioned polysulfide rubber includes hydroxyl-terminated liquid polysulfide rubber.
[0023] Obviously, based on the above content of this application, in accordance with the common technical knowledge and customary means in this field, without departing from the above basic technical ideas of this application, other various forms of modifications, replacements or changes can be made.
[0024] Beneficial technical effects of this application:
[0025] The manganese dioxide nanomaterial provided in the present application has a porous structure and contains a specific crystal form, which can provide more reactive sites for the polysulfide reaction of polysulfide rubber, and ultimately improve the performance of polysulfide rubber. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0027] Figure 1 This is a scanning electron microscope (SEM) image of the manganese dioxide material of some embodiments of the present application;
[0028] Figure 2 , Figure 3 The X-ray diffraction pattern (XRD) of the manganese dioxide material of some embodiments of the present application;
[0029] Figure 4 , Figure 5 The nitrogen adsorption-desorption curve of the manganese dioxide material of some embodiments of the present application;
[0030] Figure 6 , Figure 7 This is the macropore distribution curve of the manganese dioxide material of some examples of this application. DETAILED DESCRIPTION
[0031] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0032] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0033] Definition of terms
[0034] In this application, when there is a conflict between the name and structure of a compound, the structure of the compound shall prevail.
[0035] Unless expressly stated to the contrary, all ranges cited herein are inclusive.
[0036] The term "one" or "a" used in this application is used to describe the elements and components described in this application. This is done only for convenience and to provide a general sense of the scope of this application. This description should be understood to include one or at least one, and the singular also includes the plural, unless it is clearly indicated otherwise. "Multiple" means two or more. The numbers in this application are approximate values, whether or not the words "about" or "approximately" are used. The numerical values of the numbers may differ by 1%, 2%, 5%, 7%, 8%, 10%, etc. Whenever a number with a value of N is disclosed, any number with a value of N+ / -1%, N+ / -2%, N+ / -3%, N+ / -5%, N+ / -7%, N+ / -8% or N+ / -10% will be explicitly disclosed, where "+ / -" means plus or minus, and the range between N-10% and N+10% is also disclosed.
[0037] Polysulfide rubber has a disulfide bond on its main chain and a thiol group at the end of its side chain. Its molecular weight and cross-linking rate vary with different varieties. The polysulfide reaction of polysulfide rubber is the result of two thiol groups bonding under the participation of a curing agent, generating a disulfide polymer and releasing water as a byproduct. Common curing agents include lead dioxide, manganese dioxide, barium peroxide, calcium peroxide, etc. Polysulfide rubber is elastic and can be widely used in connection parts that produce displacement and deformation under different qualitative materials, different expansion coefficients, and different temperatures. At the same time, it also has high pressure resistance. Polysulfide rubber has good oil resistance, solvent resistance, drug resistance, aging resistance and other properties, and can be bonded to metals, ceramics, wood, cement, etc. The sealants and adhesives prepared from it have been widely used in aviation, ships, electrical appliances, construction, vehicles and other fields.
[0038] Porous compounds and porous materials based on porous compounds, such as aluminosilicate molecular sieves, have potential application value in catalysis, adsorption and separation due to their uniform and regular pore structure. In recent years, with the in-depth research on porous material chemistry and the expansion of types, transition metal oxide porous materials have certain application prospects in the fields of catalysis and electrochemistry due to the various oxidation states of transition metals. Therefore, researchers have begun to pay more attention to transition metal oxide porous materials. Among them, porous manganese dioxide materials are a typical transition metal oxide porous material. It mainly includes layered structure and pore structure. Different from the basic structure of aluminosilicate molecular sieves, porous manganese oxide materials are composed of MnO 6 The basic structural units of regular octahedron are composed of shared edges or shared angles, which further enriches and develops porous materials.
[0039] In the field of curing agents for liquid polysulfide rubber, porous manganese dioxide materials, due to their rich pore structure and pore volume, provide more reactive sites for the occurrence of polysulfide reactions, which is more conducive to adjusting the mechanical properties of liquid polysulfide rubber.
[0040] In order to achieve the above technical objectives, the first aspect of the present application is to provide a manganese dioxide nanomaterial, the material comprising manganese dioxide nanosheets, the crystal form of the manganese dioxide nanosheets comprising any one or more of delta type, alpha type, and alpha type;
[0041] The manganese dioxide nanosheets are stacked to form a porous structure, which contains macropores with a pore diameter of 300nm to 400nm.
[0042] The manganese dioxide nanosheet of the present application refers to a sheet structure with a thickness of nanometers. The crystal form of the manganese dioxide nanosheet can be determined by an X-ray diffractometer, because different crystal forms have different peak positions.
[0043] The pore size of the porous structure of the present application can be measured by conventional measurement methods in the art, such as nitrogen adsorption desorption instrument and mercury intrusion instrument. Specifically, the test instrument used is ASAP2460-physical adsorption analyzer, the material sample after drying and degassing is placed in liquid nitrogen, different test pressures are adjusted, the adsorption amount of nitrogen is measured respectively, and the adsorption and desorption isotherms are drawn. The shape of the pore is determined according to the shape of the hysteresis loop, the pore distribution is calculated according to different pore models, and the pore size distribution curve of the macropore is fitted using the BJH model.
[0044] In these embodiments, the present application discloses that the pore size of the macropores is any one of 200nm, 210nm, 213nm, 297nm, 298nm, 300nm, 310nm, 344nm, 346nm, 350nm, 365nm, 380nm, 400nm, 424nm, 442nm, 450nm, 500nm, 513nm, and 600nm, or any one of the values satisfying the above ranges.
[0045] In some embodiments, the BET specific surface area of the manganese dioxide nanomaterial is 10 m 2 / g~50m 2 / g.
[0046] The specific surface area of the manganese dioxide nanomaterial of the present application can be measured by conventional measurement methods in the art, such as using nitrogen adsorption-desorption curves.
[0047] The present application discloses in these examples that the specific surface area of the manganese dioxide nanomaterial is 10 m 2 / g, 15m 2 / g, 17.07m 2 / g, 17.34m 2 / g, 19.11m 2 / g, 20m 2 / g, 20.12m 2 / g, 22.21m 2 / g, 22.47m 2 / g, 23.56m 2 / g, 25m 2 / g, 26.32m 2 / g, 27.21m 2 / g, 29.15m 2 / g, 30m 2 / g, 33.82m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g, 50m 2 / g or any of the values satisfying the above ranges.
[0048] In some embodiments, the crystal form of the manganese dioxide nanosheets is delta-type, and the pore size of the macropores formed by stacking the manganese dioxide nanosheets is 400 nm to 600 nm.
[0049] The second aspect of the present application is to provide a method for preparing the manganese dioxide nanomaterial described in the first aspect, comprising the following preparation process:
[0050] providing a suspension of polystyrene microspheres;
[0051] Adding manganese salt to the suspension of polystyrene microspheres, mixing well, and forming a dispersion;
[0052] Add 20% to 30% by mass of ammonia water to the above dispersion, and react at room temperature to obtain a brown solid;
[0053] The brown solid is dispersed in an alkaline solution with a concentration of 0.5 mol / L to 6 mol / L, a solid is obtained by hydrothermal reaction, polystyrene microspheres on the solid are removed, and then a manganese dioxide nanomaterial is obtained by ultrasonic stripping.
[0054] The polystyrene microspheres of the present application serve as a template for the reaction and are subsequently removed by dissolution.
[0055] In some embodiments, the average particle size of the polystyrene microspheres is 400 nm to 600 nm. In the following embodiments, the present application selects microspheres with an average particle size of 450 nm to prepare the manganese dioxide porous material.
[0056] In some embodiments, polystyrene microspheres are dispersed in deionized water to form a suspension of polystyrene microspheres.
[0057] In some embodiments, the ratio of the mass of polystyrene microspheres to the volume of deionized water is (1 g to 5 g): 50 mL.
[0058] In some embodiments, the hydrothermal reaction temperature is 120° C. to 150° C., and the reaction time is 10 h to 30 h.
[0059] In these embodiments, the present application discloses that the hydrothermal reaction temperature is any one of 120°C, 130°C, 140°C, 150°C or any one of the above ranges. The reaction time is any one of 10h, 15h, 20h, 25h, 30h or any one of the above ranges.
[0060] In some embodiments, the method includes: removing the polystyrene microspheres on the solid, washing with anhydrous ethanol to obtain a liquid, and ultrasonically exfoliating the liquid; controlling the ultrasonic vibration frequency of the ultrasonic exfoliation to any frequency conventional in the art, and the processing time is 4h to 24h.
[0061] In some embodiments, the mass ratio of the polystyrene microspheres to the manganese salt is (1-5):(2-5); the manganese salt includes any one or more of manganese nitrate, manganese acetate, manganese chloride, manganese sulfate and hydrated salts thereof.
[0062] The present application discloses in these embodiments that the mass ratio of the polystyrene microspheres to the manganese salt is any one of 1:2, 1:5, 5:2, 5:5 or any one of the above ranges.
[0063] The present application discloses in these embodiments that the manganese salt includes any one or more of manganese nitrate tetrahydrate, manganese acetate dihydrate, manganese chloride tetrahydrate, and manganese sulfate monohydrate.
[0064] In some embodiments, the weight ratio of the brown solid to the alkaline solution is 1:(10-30); the alkaline solution includes an aqueous solution of any one or more of sodium hydroxide and potassium hydroxide.
[0065] In some embodiments, the weight ratio of the brown solid to the alkaline solution is any one of 1:10, 1:20, 1:30 or any one of the above ranges.
[0066] In some embodiments, the preparation of the brown solid further comprises: adding 20% to 30% by mass of ammonia water to the dispersion to react the brown suspension at room temperature. Filtering the solid to obtain the filtrate, washing it with distilled water, and then drying it, for example, at 30° C. for 24 hours to obtain a brown powder. The room temperature here refers to 20° C. to 30° C.
[0067] In some embodiments, removing the polystyrene microspheres from the solid comprises washing the solid with water until it is neutral, drying it, for example, at 60° C., soaking the dried solid in N,N-dimethylformamide, filtering, and repeating the above steps three times.
[0068] In some embodiments, the ultrasonic stripping is followed by drying, such as drying in a vacuum drying oven at 50° C. for 6 hours.
[0069] In some embodiments, the method for preparing manganese dioxide nanomaterials comprises the following steps:
[0070] (1) First, 1 g to 5 g of polystyrene microspheres are weighed and added into 50 mL of deionized water, and dispersed using an ultrasonic cleaner to form a polystyrene microsphere suspension solution;
[0071] (2) adding 2 g to 5 g of manganese salt to the suspension of step (1), and sonicating at room temperature for 5 to 20 minutes;
[0072] (3) Add 5 mL to 30 mL of aqueous ammonia (25%) to the solution in step (2), stir magnetically for 10 to 30 minutes to obtain a brown suspension. Filter the obtained precipitate, wash it thoroughly with distilled water, and then dry it at 40° C. for 24 hours to obtain a brown powder;
[0073] (4) dispersing the brown powder obtained in step (3) into 100 mL of 0.5 mol / L to 6 mol / L alkali solution, then transferring it into a 200 mL reactor and subjecting it to hydrothermal treatment at 80 to 150° C. for 24 h, neutralizing the obtained solid and drying it at 60° C.;
[0074] (5) The washed and dried solid was soaked in N,N-dimethylformamide for 6 hours, and the N,N-dimethylformamide dissolved on the polystyrene microspheres was removed by filtration. The above steps were repeated 3 times, and then the solid was filtered and washed with anhydrous ethanol for 3 to 4 times. The obtained liquid was then ultrasonically peeled for 8 hours, and then placed in a vacuum drying oven at 50°C for 6 hours. Finally, porous manganese dioxide was obtained.
[0075] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0076] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0077] Conventional techniques of inorganic chemistry within the art can be used in this application. In the following examples, efforts are made to ensure the accuracy of the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be considered. The temperatures (in degrees Celsius) used in the following examples are expressed in ° C, and the pressure is atmospheric pressure or near atmospheric pressure. All pharmaceutical reagents are purchased at AR grade, and all reactions are carried out under argon protection. Unless otherwise noted, all reagents are obtained from commercial channels.
[0078] The present application is further described below by way of examples, but is not intended to limit the present application.
[0079] Example 1
[0080] A method for preparing a manganese dioxide nanomaterial is provided, and the specific preparation process is as follows:
[0081] First, 2 g of polystyrene microspheres were weighed and added into 50 mL of deionized water, and dispersed into a polystyrene microsphere suspension solution using an ultrasonic cleaner. Then, 3.77 g of manganese nitrate tetrahydrate was added, and ultrasonic treatment was continued for 30 minutes.
[0082] Then, 20 mL of aqueous ammonia (25%) was added to the mixture, and after magnetic stirring for 20 minutes, the brown precipitate was filtered out, washed thoroughly with distilled water, and then dried at 40° C. for 24 h.
[0083] The brown powder was added to 100 mL of 2 mol / L sodium hydroxide solution (the weight ratio of the brown solid mass to the sodium hydroxide solution was controlled to be 1:22.5), then transferred to a 200 mL reactor and subjected to hydrothermal treatment at 120 °C for 24 h. The obtained solid was washed to neutrality and dried at 60 °C.
[0084] The washed and dried solid was soaked in N,N-dimethylformamide for 6 hours, and the N,N-dimethylformamide dissolved on the polystyrene microspheres was removed by filtration. After repeating the above steps 3 times, it was filtered and washed 3 to 4 times with anhydrous ethanol, and the obtained liquid was ultrasonically peeled for 8 hours, and then placed in a 50°C vacuum drying oven for 6 hours. Finally, porous manganese dioxide was obtained.
[0085] Example 2-1
[0086] A method for preparing a manganese dioxide nanomaterial is provided, which differs from Example 1 in that a hydrothermal treatment is performed at 150° C. for 24 hours, and the rest is the same as Example 1.
[0087] Comparative Example 1
[0088] A method for preparing a manganese dioxide nanomaterial is provided, which differs from Example 1 in that a hydrothermal treatment is performed at 80° C. for 24 hours, and the rest is the same as Example 1.
[0089] Example 3-1
[0090] A method for preparing a manganese dioxide nanomaterial is provided, which differs from Example 2-1 in that the brown powder is added to 100 mL of a 1 mol / L sodium hydroxide solution, then transferred to a 200 mL reactor and hydrothermally treated at 150° C. for 24 h, the resulting solid is washed to neutrality, and dried at 60° C.
[0091] Example 3-2
[0092] A method for preparing a manganese dioxide nanomaterial is provided, which differs from Example 3-1 in that the brown powder is added to 100 mL of a 1 mol / L potassium hydroxide solution, then transferred to a 200 mL reactor and hydrothermally treated at 150° C. for 24 h, the resulting solid is washed to neutrality, and dried at 60° C.
[0093] Example 3-3
[0094] A method for preparing a manganese dioxide nanomaterial is provided, which is different from Example 2-1 in that the brown powder is added to 100 mL of a 4 mol / L sodium hydroxide solution.
[0095] Embodiment 3-4
[0096] A method for preparing a manganese dioxide nanomaterial is provided, which is different from Example 2-1 in that the brown powder is added to 100 mL of a 4 mol / L potassium hydroxide solution.
[0097] Embodiment 3-5
[0098] A method for preparing a manganese dioxide nanomaterial is provided, which is different from Example 1 in that the brown powder is added to 100 mL of a 0.5 mol / L sodium hydroxide solution.
[0099] Embodiment 3-6
[0100] A method for preparing a manganese dioxide nanomaterial is provided, which is different from Example 1 in that the brown powder is added to 100 mL of a 6 mol / L sodium hydroxide solution.
[0101] Example 4-1
[0102] A method for preparing a manganese dioxide nanomaterial is provided, which differs from Example 1 in that first, 2 g of polystyrene microspheres are weighed and added to 50 mL of deionized water, dispersed with an ultrasonic cleaner to form a polystyrene microsphere suspension solution, and then 4.02 g of manganese acetate dihydrate is added, and ultrasound is continued for 30 minutes.
[0103] Example 4-2
[0104] A method for preparing a manganese dioxide nanomaterial is provided, which is different from Example 1 in that first, 2 g of polystyrene microspheres are weighed and added into 50 mL of deionized water, dispersed with an ultrasonic cleaner to form a polystyrene microsphere suspension solution, and then 2.55 g of manganese sulfate monohydrate is added, and ultrasonication is continued for 30 minutes.
[0105] Example 4-3
[0106] A method for preparing a manganese dioxide nanomaterial is provided, which differs from Example 1 in that first, 2 g of polystyrene microspheres are weighed and added to 50 mL of deionized water, dispersed with an ultrasonic cleaner to form a polystyrene microsphere suspension solution, and then 2.97 g of manganese chloride tetrahydrate is added, and ultrasonication is continued for 30 minutes.
[0107] Characterization:
[0108] (1) Using a scanning electron microscope to obtain an electron microscope image of the product of Example 1: The test equipment model is: SU8010 high-resolution cold field emission scanning electron microscope (Hitachi, Japan), and the morphology of the sample is tested at 40 kV. Figure 1 It can be seen that the manganese dioxide nanomaterial includes manganese dioxide nanosheets, and the nanosheets are stacked to form a porous structure.
[0109] (2) Obtain the XRD curves of the products of Example 3-2 and Example 3-4. The test method includes: grinding the prepared black-gray sample to obtain a finer powder sample, filling and compacting it in the XRD sample cell, and the equipment is a D8-advance X-ray diffractometer (Bruker AXS Co., Ltd., Germany). Cu Kα rays are used, the working voltage of the ray tube is 40kV, and the working current is 40mA. The scanning range is 5° to 90°, the scanning angular step is 0.02°, and the scanning speed is 3deg / min. The obtained data is processed to obtain the required data. Figure 2 , Figure 3 , combined with Figure 2 It can be seen that the R-type crystal is obtained in this embodiment. Figure 3 It can be seen that the δ crystal form is obtained in this embodiment.
[0110] (3) The nitrogen adsorption-desorption curves of the products of Example 1 and Example 2-1 were obtained. The test method included: using an ASAP 2460 tester (Micromeritics, USA), the sample needed to be placed in an oven at 300°C for 6 hours before testing, and then the nitrogen adsorption-desorption was tested at 77K.
[0111] (4) Obtaining the macropore distribution curves of the products of Example 3-1 and Example 3-2, the testing method includes: nitrogen adsorption desorption instrument.
[0112] According to the above test method, the parameter list of the remaining embodiments is obtained, as shown in the following figure:
[0113] Table 1
[0114]
[0115]
[0116] Application Examples
[0117] The present application provides a polysulfide sealant, which includes the above-mentioned manganese dioxide nanomaterial and polysulfide rubber, wherein the polysulfide rubber includes hydroxyl-terminated liquid polysulfide rubber, such as commercially available polysulfide rubber with a relative molecular weight of 1000-100000 and a mercapto content of 0.5%-8%.
[0118] The mass percentage content of the above-mentioned manganese dioxide nanomaterial in the above-mentioned polysulfide sealant is 3% to 10%, specifically any one of 3%, 4%, 4.7%, 5%, 6%, 7%, 8%, 9%, 10% or any one of the above-mentioned range values.
[0119] The specific method is as follows: 5 grams of the manganese dioxide material obtained in the above embodiment (the mass percentage content in the polysulfide sealant is 4.7%), 0.1 grams of promoting D (diphenylguanidine), are added to 100 grams of polysulfide rubber (brand JLY-155), and the above raw materials are mixed evenly using a three-roll grinder. The stress relaxation time is measured using an RPA2000 rubber processing analyzer to characterize the performance of the polysulfide process. The performance of the polysulfide process can be represented by the difference between the maximum and minimum torque values, the scorch time and the optimal curing time (the time when the maximum torque is 90%).
[0120] The following comparative example 1 selects alpha crystal manganese dioxide, supplier: Shaanxi Zhiju New Material Technology Co., Ltd.
[0121] The following comparative example 2 selects amorphous manganese dioxide, the supplier is: McLean Reagent Company.
[0122] 1. Comparison of typical elasticity curves of polysulfide rubber containing manganese dioxide curing agent prepared under different manganese sources as a function of curing time. The results are shown in Table 2.
[0123] Table 2
[0124]
[0125]
[0126] The results show that the porous manganese dioxide material prepared with manganese nitrate as the manganese source has a relatively large difference between the maximum and minimum torque values, which indicates that the porous manganese dioxide material prepared with the manganese source of the present application has a higher polysulfide process activity. At the same time, the longer coking time ensures sufficient operation time.
[0127] 2. Compare the typical elastic curves of polysulfide rubber containing different structure directing agents and manganese dioxide curing agents prepared at different structure directing agent concentrations as the curing time changes. The results are shown in Table 3.
[0128] Table 3
[0129]
[0130] The results show that compared with potassium hydroxide as a structure-directing agent, the macroporous manganese dioxide material prepared with sodium hydroxide as a structure-directing agent has a relatively large difference between the maximum and minimum torque values, that is, the macroporous manganese dioxide material prepared with sodium hydroxide as a structure-directing agent has a higher polysulfide process activity. At the same time, with the increase of the concentration of the structure-directing agent, its activity first increases and then decreases. In summary, the most suitable type of structure-directing agent is sodium hydroxide, with a concentration of 2 mol / L.
[0131] 3. The mixed mixture was placed in a 2 mm thick tensile specimen mold, vulcanized at room temperature for 24 hours, and heated at 70°C for 24 hours. The obtained tensile specimens were tested for mechanical properties using the GB / T 528-2009 method, including Shore A hardness, 100% modulus, tensile strength, and elongation at break. The results are shown in Table 4:
[0132] Table 4
[0133]
[0134] It can be seen from Table 4 that the liquid polysulfide rubber cured with the macroporous manganese dioxide of Example 1 has a lower elongation at break than the liquid polysulfide rubber cured with the macroporous manganese dioxide of other examples, but has a higher Shore A hardness and 100% modulus value. Compared with Comparative Examples 1 and 2, it also has a higher tensile strength. The product obtained after surface vulcanization has a denser cross-linking network and better performance.
[0135] The above is only a preferred specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A manganese dioxide nanomaterial, characterized in that: It includes manganese dioxide nanosheets, wherein the crystal form of the manganese dioxide nanosheets includes any one or more of delta type, alpha type and alpha type; The manganese dioxide nanosheets are stacked to form a porous structure, and the porous structure comprises macropores, and the pore diameter of the macropores is 200nm to 600nm.
2. The manganese dioxide nanomaterial according to claim 1, characterized in that: The specific surface area of the manganese dioxide nanomaterial is 10 m 2 / g~50m 2 / g.
3. The manganese dioxide nanomaterial according to any one of claims 1 to 2, characterized in that: The crystal form of the manganese dioxide nanosheets is delta-type, and the pore size of the macropores formed by stacking the manganese dioxide nanosheets is 400nm-600nm.
4. A method for preparing a manganese dioxide nanomaterial according to any one of claims 1 to 3, characterized in that: The preparation process includes the following: providing a suspension of polystyrene microspheres; adding manganese salt to the suspension of polystyrene microspheres, mixing well, and forming a dispersion; Adding 20% to 30% by mass of ammonia water to the dispersion, reacting at room temperature to obtain a brown solid; The brown solid is dispersed in an alkaline solution with a concentration of 0.5 mol / L to 6 mol / L, a solid is obtained by hydrothermal reaction, polystyrene microspheres in the solid are removed, and then a manganese dioxide nanomaterial is obtained by ultrasonic stripping.
5. The preparation method according to claim 4, characterized in that: The hydrothermal reaction temperature is 120° C. to 150° C., and the reaction time is 10 h to 30 h.
6. The preparation method according to claim 4, characterized in that: The method comprises: removing the polystyrene microspheres on the solid, washing with anhydrous ethanol to obtain a liquid, and ultrasonically peeling the liquid; The ultrasonic peeling treatment time is controlled to be 4 hours to 24 hours.
7. The preparation method according to claim 4, characterized in that: The mass ratio of the polystyrene microspheres to the manganese salt is (1-5):(2-5); the manganese salt includes any one or more of manganese nitrate, manganese acetate, manganese chloride, manganese sulfate and hydrated salts thereof.
8. The preparation method according to claim 4, characterized in that: The weight ratio of the brown solid to the alkaline solution is 1:(10-30); the alkaline solution includes an aqueous solution of any one or more of sodium hydroxide and potassium hydroxide.
9. A polysulfide sealant, characterized in that: The invention comprises the manganese dioxide nanomaterial according to any one of claims 1 to 3 or the manganese dioxide nanomaterial prepared by the preparation method according to any one of claims 4 to 8, and also comprises polysulfide rubber.
10. The polysulfide sealant according to claim 9, characterized in that: The mass percentage of the manganese dioxide nanomaterial in the polysulfide sealant is 3% to 10%; and / or; The polysulfide rubber includes hydroxyl-terminated liquid polysulfide rubber.
Citation Information
Cited By
High-activity manganese dioxide for curing polysulfide rubber and method for preparing the same
CN122704982A
